Synthesis and biological activity of aminophthalazines and aminopyridazines as novel inhibitors of PGE(2) production in cells - Medda, Federico (2012)
This article reports the synthesis and biological evaluation of a collection of aminophthalazines as a novel class of compounds capable of reducing production of PGE(2) in HCA-7 human adenocarcinoma cells. A total of 28 analogs were synthesized, assayed for PGE(2) reduction, and selected active compounds were evaluated for inhibitory activity against COX-2 in a cell free assay. Compound 2xxiv (R(1) = H, R(2) = p-CH(3)O) exhibited the most potent activity in cells (EC(50) = 0.02 µM) and minimal inhibition of COX-2 activity (3% at 5 µM). Furthermore, the anti-tumor activity of analog 2vii was analyzed in xenograft mouse models exhibiting good anti-cancer activity.